Android-based Teaching Material for Statistics Integrated with Social Media WhatsApp - Prabowo, Anggit; Rahmawati, Uki; Anggoro, Rostien Puput (International Journal on Emerging Mathematics Education, 2019)
The purpose of this study was to develop teaching material in the form of Android-based application for junior high school mathematics subjects in statistical material that are integrated with WhatsApp social media platform. The procedure for developing teaching materials was carried out through the stages of defining, designing, developing, and disseminating. The platform used to develop teaching material was MIT App Inventor. The teaching materials developed have been validated by two media experts and material experts. The trial of teaching material was carried out to educators and prospective mathematics educators in the Special Region of Yogyakarta and students at Depok 3 State Junior High School. This study has succeeded in developing Android-based teaching materials for junior high school mathematics subjects in valid and effective statistical material. The menus contained in this application consist of material and competency test. On the competency test menu, students can do the test and after completion, the application will display the score of the test results. What interesting about this application, the test results can be sent to the teacher via WhatsApp.